Proses Komunikasi melalui Media Visual Fotografi sebagai Ilustrasi - Agnes Paulina Gunawan (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2021)
Artwork generally contains a message or idea to be communicate to others as a viewer. From the various situations that can be captured in a visual appearance of the work of Photography, many things can be delivered into an idea that can have different meanings depending on the impression captured by the photographer and also depending on the interpretation of the viewer. However, considering the work of Photography as a visual work in two-dimensional form, of course there are advantages and disadvantages of expressing ideas or meanings that the photographer might want to deliver, so maybe there is different perception, and not everybody can clearly understand the intent and impression the photographer means. Different interpretations from the photographer's point of view and the point of view of the observer are actually relatively reasonable, considering that each person with different emotional experiences and from different points of view can produce different reactions. With the visual appearance of the photography work, many people use this visual information to explain some information. Either in articles, in stories, or in a work procedures or processes. So that the photo works will be a tool to support, to clear up and clarify information. This journal will discuss about photography as a visual media that support an information commonly known as Illustration Photography.